CLINICAL FEATURES AND OUTCOME IN CHILDREN WITH LANGERHANS CELL HISTIOCYTOSIS. A SINGLE INSTITUTION EXPERIENCE FROM PAKISTAN - Nida Noor; Rabia Muhammad wali; Annis -Ur- Rehman; Muhammad Abu Bakar (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out the clinical manifestations, treatment given and outcome of children with diagnosis of Langerhans cell histiocytosis.